Evolution of gender stereotypes in Spain: traits and roles - Morales, J. Francisco; López-sáez, Mercedes; Lisbona, Ana (The Spanish Journal of Psychology, 2008)
The aim of this study is twofold: to determine whether (and how) gender stereotypes have changed over time through a comparison of two different sets of data collected in 1993 (N = 1255) and 2001 (N = 1255) from a representative sample of the Spanish population, and to examine the relation between gender traits and roles and its stability over time. In addition, special attention is paid to the psychometric properties of the measures of gender traits and roles used in the study. The content of gender stereotypes was found to remain stable over the target period of time, confirming the classical typology (a higher assignment of expressive-communal traits to women and of instrumental-agentic traits to men). The structure of the gender-role questionnaire allows us to distinguish between family-role and work-role stereotyping. Gender-role stereotyping shows a marked decline between 1993 and 2001, a result that contrasts with the stability of trait-role stereotyping. The fact that a very low correlation is observed at the two time points between these two components of gender stereotyping strongly suggests their independence.